2006
DOI: 10.1002/jclp.20332
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of personal construct therapy: A comprehensive review

Abstract: Prior narrative and quantitative reviews have suggested that personal construct therapy (PCT) is an efficacious and viable form of treatment. However, these reviews failed to include all published, controlled PCT outcome studies and did not account for all measures of outcome. The present quantitative review, therefore, offers a comprehensive integration of the 22 published studies that compare PCT to a control group, examining its overall efficacy at posttest and follow-up as well as its effects for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
1
14
1
1
Order By: Relevance
“…Neimeyer and colleagues (Holland, Neimeyer, Currier, & Berman, 2007;Neimeyer, Heath, & Strauss, 1985;Neimeyer, Klein, Gurman, & Griest, 1983) have found that negative constructions of the future self are particularly related to the severity of depressive symptoms and decrease following personal construct cognitive therapy. Given the emphasis on anticipatory processes and core constructions of the self in personal construct theory, therapists may want to consider including the future self as an element in RepGrid assessment.…”
Section: Discussionmentioning
confidence: 95%
“…Neimeyer and colleagues (Holland, Neimeyer, Currier, & Berman, 2007;Neimeyer, Heath, & Strauss, 1985;Neimeyer, Klein, Gurman, & Griest, 1983) have found that negative constructions of the future self are particularly related to the severity of depressive symptoms and decrease following personal construct cognitive therapy. Given the emphasis on anticipatory processes and core constructions of the self in personal construct theory, therapists may want to consider including the future self as an element in RepGrid assessment.…”
Section: Discussionmentioning
confidence: 95%
“…More often than not, the client was seen by a female therapist. Further details about the descriptive characteristics of these studies have been reported in another publication (Holland et al, 2007).…”
Section: Studiesmentioning
confidence: 97%
“…Despite the intuitive appeal of these novel interventions and other related techniques (Neimeyer & Bridges, 2003), a recent meta-analysis of the PCT outcome literature revealed an average effect size of .38 when PCT was compared to a waitlist control group, placebo, or standard care (Holland, Neimeyer, Currier, & Berman, 2007). 1 Although this effect was significantly greater than zero, it was notably smaller than those found for psychotherapy in general, which have shown average effect sizes ranging from about .75 to .85 (Wampold, 2001).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…There are similarities between elements of PCT and many other therapies (e.g., cognitive behavioural therapy, solution-focused therapy, dialectical behaviour therapy, narrative therapy, and with systemic approaches). Personal construct psychotherapy has been found to have positive results with adults (Holland, Neimeyer, Currier, & Berman, 2007, Metcalfe, Winter, & Viney, 2007. The use of PCP with children and adolescents has more often been described in the literature of educational psychology and teaching (e.g.…”
Section: Introductionmentioning
confidence: 96%